Development of a firm export performance measurement model using a hybrid multi-attribute decision-making method - Dahooie, Jalil Heidary; Meidute-Kavaliauskiene, Ieva; Vanaki, Amir Salar; Podviezko, Askoldas; Beheshti Jazan Abadi, Elham (Management decision, 2020)
PurposeThe present study is aimed to develop a firm export performance measurement model. Increased levels of globalization are forcing firms, especially SMEs (i.e. small and medium-sized enterprises) and entrepreneurial firms, to enter new markets and increase their exports. Consequently, export performance measurement has become a vital tool for achieving competitive advantages, and this type of measurement is considered an important topic of research in the field of international marketing. However, the literature lacks a comprehensive framework for measuring export performance, even though many criteria for gauging this performance's parameters have been discovered and applied.Design/methodology/approachA literature review was conducted, and the most important criteria for export performance measurement was identified using weights obtained by stepwise weight assessment ratio analysis method. Then, the export performance of five firms was evaluated using the additive ratio assessment method with interval-valued triangular fuzzy numbers.FindingsThe 15 most significant criteria were identified and categorized into three dimensions: economic, strategic, and other. The strategic dimension was identified as the most important, while the criteria “strategic goals achievement” and “return on investment” were found to be the most relevant.Practical implicationsA comprehensive framework including a definitive set of the most prominent, useful evaluation criteria was established which enables both scholars and practitioners to assess export performance.Originality/valueThe current study attempts to fill the gaps in the literature by presenting a comprehensive framework for export performance measurement.